The Prognostic and Immunological Value of Guanylate-Binding Proteins in Lower-Grade Glioma: Potential Markers or Not? - Liu, Zhuang; Sun, Jifeng; Gong, Ting; Tang, Huixin; Shen, Yanna; Liu, Chang (Frontiers in Genetics, 2021)
Seven guanylate-binding proteins (GBPs, GBP1-7), identified as a subfamily of interferon-γ-induced guanosine triphosphate hydrolases (GTPases), has been reported to be closely associated with tumor progression, metastasis and prognosis of cancer patients in recent years. However, the expression patterns, prognostic value, immune infiltration relevance and biological functions of GBPs in lower-grade glioma (LGG) remain elusive. In this study, by analysis and verification through multiple public data platforms, we found that GBP1, 2, 3, 4 were significantly up-regulated in LGG tissues vs. normal brain tissue. Analysis based on the Cox proportional hazard ratio and Kaplan-Meier plots demonstrated that the high expressions of GBP 1, 2, 3, 4 were significantly correlated to the poor prognosis of LGG patients. Correlation analysis of clinical parameters of LGG patients indicated that the expressions of GBP 1, 2, 3, 4 were significantly associated with the histological subtype and tumor histological grade of LGG. Furthermore, the correlation analysis of immune infiltration showed that the expressions of GBP1, 2, 3, 4 were significantly and positively correlated with the level of tumor immune infiltrating cells. In particular, GBP1, 2, 3, 4 expressions were strongly correlated with the infiltration levels of Monocyte, TAM, M1/M2 macrophage, revealing their potential to regulate the polarity of macrophages. Finally, we used the GSEA method to explore the signaling pathways potentially regulated by GBP1, 2, 3, 4, and found that they were all closely associated with immune-related signaling pathways. Collectively, these findings suggested that GBP1, 2, 3, 4 were potent biomarkers to determine the prognosis and immune cell infiltration of LGG patients.